Masjid Lerabaing: Kearifan Lokal Dalam Penyiaran Islam Di Nusa Tenggara Timur - Fahrudin, Ali (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2020)
At-Taqwa Lerabaing Mosque is one of the ancient mosques in Alor Island, Nusa Tenggara Timur (NTT). By revealing the history of mosque establishment, it is hoped that it can reveal the history of Islam coming to NTT, which is currently predominant Christian and Catholic. This study aims to preserve the cultural heritage of the Indonesian Nation, especially related to the historic mosque and its role in spreading Islam in the Alor Regency, NTT. This study uses a historical-archaeological approach. Performing this research, it is expected to reveal the origin of the mosque, the condition of the community at the time of its construction, the architecture and the historical objects contained therein, and local wisdom in broadcasting Islam in NTT. The results of this study reveal that the history of the coming Islam to Alor Island was closely related to the arrival of a preacher from Ternate named Sultan Kimales Gogo. After the King of Kui Kingdom and his people converted to Islam, he established this mosque. The mosque in the form of a house on stilts was built in 1042 H or 1633 M. Compared to other mosques in Indonesia, this mosque has its specificity. it lies in its shape which resembles a stage house with a two-story roof and all materials made from wood and bamboo without nails. Keywords: Alor Island, Nusa Tenggara Timur, Lerabaing mosque. Â Masjid At-Taqwa Lerabaing adalah salah satu masjid kuno yang ada di Pulau Alor, Nusa Tenggara Timur (NTT). Tulisan ini bertujuan untuk mengungkap sejarah pendirian masjid At-Taqwa, Lerabaing dan sejarah masuknya agama Islam di Provinsi NTT. Hal ini merupakan upaya melestarikan warisan budaya Bangsa Indonesia, khususnya yang berkaitan dengan masjid bersejarah dan perannya dalam penyiaran Islam di wilayah Kabupaten Alor, Nusa Tenggara Timur. Penelitian eksploratif deskriptif ini menggunakan pendekatan historis-arkeologis. Beberapa hal yang ditelaah adalah asal usul berdirinya masjid, kondisi masyarakat pada saat pendiriannya, arsitektur dan benda-benda bersejarah yang ada di dalamnya, serta kearifan lokal dalam penyiaran Islam di NTT. Kajian ini menunjukkan bahwa sejarah masuknya Islam di Pulau Alor erat kaitannya dengan kedatangan pendakwah dari Ternate yang bernama Sultan Kimales Gogo. Setelah berhasil mengislamkan Raja Kerajaan Kui dan rakyatnya, Sultan Kimales Gogo mendirikan masjid At-Taqwa. Masjid yang berbentuk rumah panggung ini dibangun pada tahun 1042 H atau 1633 M. Kekhasan masjid ini dibandingkan masjid-masjid lainnya di Indonesia terletak pada bentuknya yang menyerupai rumah panggung dengan atap bertingkat dua dan semua bahannya terbuat dari kayu dan bambu tanpa paku. Kata kunci: masjid Lerabaing, Nusa Tenggara Timur, Pulau Alor